Operational risk categorization in project-based organizations: A theoretical perspective from a project portfolio risk lens - Micán, Camilo (2019)
Project-based organizations have their processes based on project, program and portfolio approach, they work within a multi-project environment and their core activities are carried out through project execution under an integrated organizational project management. Therefore, operational risks in project-based organizations are directly related to the project risk management. Thus, in project-based organizations risk management is not only about project risk management, because literature also shows that risk management applied to each project in an isolated way is not enough for systemic risk management in project portfolio and organizational context. This paper, based on a systematic literature review on project portfolio risk management, identifies project portfolio risk categories proposed in previous studies, and proposes and describes four categories associated to operational risk in project portfolio context: project portfolio management level, environmental conditions, project interactions and internal processes. The categories proposed for operational risk in project-based organizations under project portfolio approach are oriented to risk management focused not on the operational risk of each isolated project, but on the project portfolio management. The results can be considered a partial contribution towards building conceptual elements to support project portfolio management process.